Metallisation of polymers and polymer matrix composites by cold spray: state of the art and research perspectives. (19th May 2022) - Parmar, Hetal; Tucci, Fausto; Carlone, Pierpaolo; Sudarshan, T. S.
ABSTRACT: Surface treatments on polymer-based materials are frequently used to enhance mechanical and physical properties. Cold spray is a metallisation technique that provides a viable solution to overcome the main drawbacks of conventional thermal spray processing techniques related to surface degradation at high temperatures. This review provides a critical overview on the metallisation of polymers and polymer matrix composites using cold spray. It offers an informative read on different approaches, bonding mechanisms, spraying procedures and parameters that influence the deposition efficiency, and the features of the coating. The future scope section broadly highlights potentially relevant areas for further developments using the method for metallising polymer-based substrates. GRAPHICAL ABSTRACT: UF0001